Implementation of the Reading to Learn Model to Improve Numeracy Literacy Skills at Smp Negeri 2 Suwawa - Ismail, Sri Rahmawati; Nurwan, Nurwan; Kobandaha, Putri Ekawaty (FKIP - Universitas Riau, 2025)
Education today emphasizes the importance of numeracy literacy as part of the basic competencies in the Merdeka Curriculum. Numeracy literacy is an essential skill for students to understand and use mathematics in real-life contexts. This study aims to examine the influence of the Reading to Learn learning model on students' mathematical numeracy literacy skills in statistical material. This study uses a quantitative approach with a post-test-only control group design. Two eighth-grade classes at SMP Negeri 2 Suwawa were randomly selected as the sample. The experimental class was taught using the Reading to Learn model, while the control class received conventional instruction. The research instrument is an essay test that has been validated to measure mathematical numeracy literacy. Data analysis shows that the distribution is normal and the variance is homogeneous. The independent samples t-test revealed a significant difference between the post-test scores of the two groups, with the experimental class achieving a higher average. The effect size, calculated using Cohen's d, is 3.53, indicating a strong effect. These results indicate that the Reading to Learn model significantly improves students' mathematical numeracy literacy. This model helps students understand concepts contextually, think critically, and actively participate in learning.